Solar extractive metallurgy for the production of Mg and Zn from carbothermal reduction of MgO and ZnO at low pressure in a solar thermochemical reactor - Srirat Chuayboon; Stphane Abanades (My University, 2022)
Solar thermochemical pyro-metallurgical process is an attractive prospect for the sustainable conversion of both metal oxides and sunlight into value-added chemicals. In this work, a comparative study of carbothermal reduction of ZnO and MgO was performed in a 1.5 kWth directly-irradiated solar reactor utilizing concentrated sunlight. Important operating parameters were studied during the experiments including the type of carbon reducing agent (activated charcoal and carbon black) in batch and continuous operating modes under both reduced (0.11-0.40 bar) and atmospheric (0.90 bar) pressures in the operating temperature range of 600-1600°C, demonstrating the solar reactor flexibility, reliability, and robustness. As a result, regarding batch tests, a decrease in the total pressure promoted the conversion of ZnO and MgO above 78% and 99%, respectively, which in turn increased Zn and Mg yields. Nevertheless, an increase in the CO2 with decreasing total pressure was observed, especially in the case of ZnO reduction, due to reduced gas residence time. In contrast, CO2 yield remained negligible in the case of MgO. Regarding continuous tests, an increase of gas production yields as well as reaction extent through the increase of reactant feeding rate was highlighted. Employing activated charcoal showed higher conversion of both ZnO and MgO, resulting from the higher available specific surface area for chemical reactions. Finally, high-purity Zn and Mg content in the solar-produced powders were achieved.
Keywords: Carbothermic reaction; Carbon fibers; Operating temperature; Chemical Looping and Thermochemical Processes